Decreased Polysaccharide Feruloylation Compromises Plant Cell Wall Integrity and Increases Susceptibility to Necrotrophic Fungal Pathogens - Reem, Nathan T.; Pogorelko, Gennady; Lionetti, Vincenzo; Chambers, Lauran; Held, Michael A.; Bellincampi, Daniela; Zabotina, Olga A. (Frontiers in Plant Science, 2016)
The complexity of cell wall composition and structure determines the strength, flexibility, and function of the primary cell wall in plants. However, the contribution of the various components to cell wall integrity and function remains unclear. Modifications of cell wall composition can induce plant responses known as Cell Wall Integrity control. In this study, we used transgenic expression of the fungal feruloyl esterase AnFAE to examine the effect of post-synthetic modification of Arabidopsis and Brachypodium cell walls. Transgenic Arabidopsis plants expressing AnFAE showed a significant reduction of monomeric ferulic acid, increased amounts of wall-associated extensins, and increased susceptibility to Botrytis cinerea, compared with wild type. Transgenic Brachypodium showed reductions in monomeric and dimeric ferulic acids and increased susceptibility to Bipolaris sorokiniana. Upon infection, transgenic Arabidopsis and Brachypodium plants also showed increased expression of several defense-related genes compared with wild type. These results demonstrate a role, in both monocot and dicot plants, of polysaccharide feruloylation in plant cell wall integrity, which contributes to plant resistance to necrotrophic pathogens.